Water management and evolutionary study for sustainable development in the Piura region, Peru - Alburqueque, Miguel (2021)
The objective was to propose a sustainable water management model based on an evolutionary study for sustainable development in the Piura region. This work was carried out under the hypothetical deductive paradigm, of a basic substantive type with a cross-sectional correlational design. Two questionnaires were used: questionnaire 1, applied to a sample of 220 families, to obtain information on water consumption, and questionnaire 2, applied to a sample of 36 professionals in the exercise of public administration, these instruments were complemented with bibliographic cards. The chi-square test (X2), degrees of freedom = 32) was used with a significance level of 5% (α = 0.05) in order to demonstrate the hypotheses raised. Confronting the values obtained experimentally, the null hypothesis was rejected. The management model and the evolutionary study of water do contribute to the sustainable development of water.